2021
DOI: 10.3390/instruments5020017
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Modeling and Design of Photon Energy Attenuation Layers for >10× Quantum Yield Enhancement in Si-Based Hard X-ray Detectors

Abstract: High-energy (>20 keV) X-ray photon detection at high quantum yield, high spatial resolution, and short response time has long been an important area of study in physics. Scintillation is a prevalent method but limited in various ways. Directly detecting high-energy X-ray photons has been a challenge to this day, mainly due to low photon-to-photoelectron conversion efficiencies. Commercially available state-of-the-art Si direct detection products such as the Si charge-coupled device (CCD) are inefficient for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Three CMOS image sensors were taped out towards this goal, as shown in Figure 2. During the phase one of this research [4], theoretical modeling and preliminary tests demonstrated more than 10× quantum efficiency improvement for high-energy X-ray photons (>10 keV) by depositing a photon-attenuation-layer (PAL) on a CMOS image sensor [5,6]. In the phase two of this research, a block-wise compact readout architecture based on unit-length-capacitor and asynchronous successive-approximation (SAR) analog to digital converter (ADC) [7] was proposed and implemented, which enabled the image sensor fabricated using a standard 180-nm process to run at 76 thousand-frames-per-second (kfps).…”
Section: Ultrafast Cmos Image Sensor Developmentmentioning
confidence: 99%
“…Three CMOS image sensors were taped out towards this goal, as shown in Figure 2. During the phase one of this research [4], theoretical modeling and preliminary tests demonstrated more than 10× quantum efficiency improvement for high-energy X-ray photons (>10 keV) by depositing a photon-attenuation-layer (PAL) on a CMOS image sensor [5,6]. In the phase two of this research, a block-wise compact readout architecture based on unit-length-capacitor and asynchronous successive-approximation (SAR) analog to digital converter (ADC) [7] was proposed and implemented, which enabled the image sensor fabricated using a standard 180-nm process to run at 76 thousand-frames-per-second (kfps).…”
Section: Ultrafast Cmos Image Sensor Developmentmentioning
confidence: 99%
“…Additionally, the number of photoelectrons generated before impact ionization divided by the number of incident photons, called the quantum yield (QY), is a useful parameter to compare to existing technologies. The QY of 1 µm PAL, 20 keV X-rays, and 50 µm Si is ~20%, much greater than the <5% using the silicon direct detection method [3,12]. A similar technology using a photocathode only obtained 5% photoelectron generation with 7.5-keV photons [13].…”
Section: Pal-si Simulationsmentioning
confidence: 99%
“…As previously mentioned, MCNP does not specify the number of photons exiting the PAL orthogonally, which may lead to an overestimation of the QY. On the other hand, MCNP's default cutoff photon energy value is below roughly 1 keV, which may underestimate the QY [3]. However, recent experimental results awaiting publication demonstrate significant relative signal enhancement from the Si reference.…”
Section: Pal-si Simulationsmentioning
confidence: 99%
See 2 more Smart Citations